La inclusión de la perspectiva de género como desafío pedagógico para el Derecho Agrario - Miranda, Marisa A. (2019)
Abstract: Among the different problems included in the imperious necessity of a juridical approach in gender perspective, we highlight here the particular social positioning of women in agricultural areas as well as its legal impact. In this sense, and considering that the agricultural activity has always been thought from a patriarchal matrix, this analysis currently becomes more significant. Having said that, the goal of this article is to exhume, from a juridical hermeneutic supported on an exploratory methodology, the treatment given to rural women and, then, focus both on gender perspective inclusion in the curricular design and, from there,on the teaching-learning process of Agrarian Law. To achieve this, it is fundamental to take into account the presence of a particular discipline characteristic: the dynamicity of its object of study; this circumstance makes the proposed didactic challenge even more complex.